A rare case of syphilis associated with renal and hepatic involvement - Alin Laurentiu Tatu; Maria Popescu; Radu Rotarescu; Sanda Dorina Popescu (Mattioli1885, 2013)
We present an unusual case of syphilis that despite starting treatment with penicillin has evolved with renal complications. Due to glomerulonephritis with nephrotic syndrome the case required shared care between the renal physician and dermatologist. Doctors of different specialties need to keep in mind that early syphilis can have visceral involvement and patients might need prompt, specific therapeutic intervention.